A Ten-year Survey of Bacterial Pathogens in Fresh, Unprocessed Fruits and Vegetables Produced, Imported, or Traded in the Netherlands - Thomas De Bock; Liesbeth Jacxsens; Frank Devlieghere; Mieke Uyttendaele (Journal of Food Protection)
Foodborne outbreaks have raised concern about the microbial safety of fresh produce. Comprehensive data on key bacterial pathogens in these products remain scarce. This study explores the prevalence of foodborne pathogens in unprocessed fruits and vegetables, focusing on the variability according to a temporal scale, the geographical origin, and the product type. A total of 12,808 fresh produce samples were collected over a period of ten years (2013–2022) and analyzed for Salmonella spp., Shiga-toxin−producing E. coli (STEC), L. monocytogenes, presumptive B. cereus, and coagulase-positive staphylococci. Overall, L. monocytogenes was the main pathogen detected (1.37%; 95% CI: 1.16–1.57%; n = 12,227), although only one sample exceeded the unsatisfactory threshold limit of 100 CFU/g. Enteric pathogens were less often detected, with a prevalence of 0.11% (95% CI: 0.05–0.17%; n = 11,538) and 0.02% (95% CI: 0.00–0.05%; n = 12,601) for STEC and Salmonella spp., respectively. Elevated levels (>100,000 CFU/g) of presumptive B. cereus were found in 0.34% (95% CI: 0.18–0.51%; n = 4,954) of cases, while coagulase-positive staphylococci were detected (>100 CFU/g) in 0.26% (95% CI: 0.11–0.42%; n = 4,169) of samples, with a maximum concentration of 190 CFU/g. The prevalence of L. monocytogenes fluctuated over time, varying from a minimum of 0.69% in 2022 to a maximum of 2.03% in 2017 and showing a seasonal effect, with an increased prevalence in June and from September to December. The major produce-pathogen combinations were L. monocytogenes and mushrooms (10.19%; 95% CI: 6.89–13.48%; n = 324) and head brassica (6.85%; 95% CI: 4.15–9.55%; n = 336); as well as STEC and legumes (0.47%; 95% CI: 0.00–1.39%; n = 213) and leafy brassica (0.40%; 95% CI: 0.00–1.17%; n = 252). This study provides valuable information for stakeholders, including farmers, distributors, retailers, and policymakers to be used in risk assessment.